Beyond the walls of the classroom: the psychodynamics of professional commitment and job involvement among female primary school teachers - Su, Qiaolan (Frontiers in Psychology, 2024)
This research used structural equation modeling (SEM) to explore the relationship between professional commitment, self-efficacy, psychological resilience, perceived organizational support and job involvement of female teachers in Chinese primary schools. The purpose of the study was to understand how these psychological and organizational factors work together on teachers' job involvement. Based on the questionnaire survey of 596 female teachers in primary schools, the data were collected and analyzed by AMOS software. The results show that professional commitment plays a central role in teachers' job involvement, and self-efficacy and psychological resilience, as important psychological resources, significantly affect job involvement through the mediation of perceived organizational support. The model fitting indicators CFI, RMSEA and SRMR were in line with the acceptance criteria, which verified the adaptability of the hypothesis model. The findings not only reinforce the application of resource conservation theory in the field of education, but also provide school administrators with strategies to improve teachers' job involvement, especially by enhancing the importance of organizational support and resilience. In addition, the results have practical implications for the design of targeted teacher professional development programs.